AN UPDATE TREATMENT OF ERITEMA NODOSUM LEPROSUM - Indah Puspasari, Ni Made; Octora Young Amukty, I Nyoman Fidry (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Leprosy, also called Morbus Hansen, is a contagious skin disease caused by the bacterium Mycobacterium Leprae. It takes 2–5 years for the disease to show up, and it takes 2–3 weeks for the cells to divide. Leprosy reaction is a sudden event that happens during the long-term course of the disease. It causes skin sores to become very red and swollen. This disease can show up before, during, or after treatment for leprosy, and it can happen to 30–50% of people with leprosy. Reactions to leprosy happen when both cellular and humoral immune responses go wrong. Type 2 or Eritema Nodosum Leprosum (ENL) reactions have a clinical picture of the appearance of nodules in the skin. This reaction occurs in leprosy patients with very large numbers of bacteria, namely the multibacillary type. In contrast to the reversal reaction, the humoral immune response plays an important role in the pathogenesis of ENL. Large amounts of bacterial antigen concentrations in tissues will increase IgM and IgG titers in multibacillary leprosy patients. Th2 cell activation will stimulate the production of IL-4 and IL-10, thereby increasing the humoral immune response and increasing the production of B lymphocytes. The goals of the treatment are to control the inflammation, ease the pain, and stop new cases from happening. In weak cases of ENL, the best way to treat it is to rest and take anti-inflammatory drugs. Most of the time, people take aspirin, which is an anti-inflammatory drug. Other drugs have also been tried, including nonsteroidal anti-inflammatory drugs (NSAIDs), colchicine, oral zinc, pentoxifylline, and chloroquine. But each of the current treatment options has its own downsides and limitations, and the best one must be carefully chosen for each case.